Analysis and improvement of the procurement process in a biotech startup - Teixeira, Sara Filipa Costa (2022)
The increasing competitiveness on the market influenced companies to adopt diferentiating strategies that bring advantage over their competitors. Procurement, which used to be seen as an operational function, is now seen as a strategic activity that deserves increasing attention. The project characterized on this report aims to analyze and improve the procurement process in a biotech startup that is still in the early stages of its life-cycle. To facilitate the analysis of the as-is process, BPMN 2.0 was used to model the process and identify how and where the data is stored, as well as the main informations flows. Two main issues were highlighted: the wastes present on the information flows and the lack of a consistent new supplier selection method. To strike the identified issues related to the information management, and mitigate its associated risks, a procurement software was developped. The Rational Unified Process (RUP) methodology was followed through the development of the software and the UML language was used to model its structure and functions. The software development entailed the integration of Microsoft Power Apps, Microsoft Power Automate and SharePoint. The developped software aggregates all the information regarding the procurement process, and allows the user to register new information as well as consult stored data. To solve the lack of a supplier-selection method issue, new criteria and subcriteria, that are alligned with the company’s strategy, for the selection of vendors were defined. Later, the TOPSIS method, which compares a set of different alternative suppliers, was applied. The development of this platform allowed the company to integrate several data sources in one complete and structured information system. This way, the paper documents, as well as the old-fashioned disorganized excel files could be completely eliminated, favoring company’s flow of data and information, which enabled a much more efficient and effective decision making. This contributed to a greater consistency of organizational knowledge in the company, since a more streamlined and agile repository of information was created.